Determinasi Kualitas Layanan, Prosedur Layanan, Lingkungan Kerja dan Implementasi Kebijakan Terhadap Kepuasan Masyarakat pada Samsat Kota Palembang Sumatera Selatan - M. Thoyib; Indra Satriawan; Farida Husin; Tutik Pebrianti; Satria P. (MBIA, 2019)
Efforts to support the provision of fast public services, for that we need a government system that supports the creation of quality public service delivery. This research was conducted to determine the factors that determine and influence community satisfaction in Palembang City samsat. The factors studied were the influence of service quality, service procedures, work environment, and policy implementation on community satisfaction partially and simultaneously. This research was collected by sampling techniques using purposive sampling which is part of nonprobability sampling with the help of research instruments in the form of 124 sheets / respondents which were distributed directly to the SAMSAT Office of Palembang City aimed directly at the people in the office. in this study analyzed using multiple linear regression models with the help of SPSS version 22.0 software. The results are estimated to have the effect of independent variables on dependents both partially and simultaneously. The dominant coefficient of influence on satisfaction is Policy Implementation of 0.288 and the lowest is the service procedure of 0.181. The independent variable can explain 48% (R2, RSquare) and the remaining 52% is influenced by other factors not included in this study.